Optimalisasi Usaha Kecil Menengah melalui Pelatihan Digital Marketing - Sasa, Saudah; Sapto Adi, Dodot; Triono, Maulid Agung; Supanto, Fajar (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2021)
The conditions faced by small industries during this pandemic are almost the same as the conditions of the industrial society as a whole. But what distinguishes it is the struggle in producing to marketing products independently. Currently, digital marketing training for small industries provides a measurable support system, due to tactical steps to market products or services to consumers with new breakthroughs. The purpose of this training is to provide easier steps to implement digital marketing applications based on information and communication technology, in order to create consumer attraction for products. The method of implementing this activity is discussion and practice of making captions on social media, online marketing, practicing product photos, forming working groups and presentations. The result of this training is that the participants have awareness of the application of digital marketing to improve the quality of product marketing for small industries more easily.